O.R. tambo district municipality communities’ perception of the municipal disaster management Centre services - ZOKO, Mxolisi Israel (Edelweiss Applied Science and Technology, 2025)
Numerous disasters have occurred in the OR Tambo district municipality over the years, affecting the lives of those residing within the district. Heavy floods, storms, and droughts are just a few of these catastrophes. Despite ongoing efforts to extend essential services to impoverished urban and rural communities, many people live in conditions of chronic disaster vulnerability, in ecologically fragile or marginal areas, where they face recurrent natural disasters and other threats. This paper focuses on exploring community perceptions within the OR Tambo district municipality’s Municipal Disaster Management Centre, utilizing constructionism theory and the new public management model to support the theoretical framework. Using a case study research design and a qualitative approach, the study employed purposive sampling to select 20 participants. Data was collected through detailed interviews and analyzed using thematic content analysis. Findings revealed that the OR Tambo District Municipality’s Municipal Disaster Management Centre is neither effective nor efficient in its disaster response. The ineffectiveness was attributed to a generalized response approach rather than tailored strategies for different disasters, along with poor response times. The study recommends that the OR Tambo MDMC enhance its capacity during disasters by improving relationships with communities, enhancing communication, and collaborating with various stakeholders to improve service delivery to the people.